All‐Dielectric Layered Photonic Topological Insulators - Chen, Xiao‐Dong; He, Xin‐Tao; Dong, Jian‐Wen (Laser & photonics reviews, 2019)
The recent realization of photonic topological insulators has brought the discovery of fundamentally new states of light and revolutionary applications such as nonreciprocal devices for photonic diodes and robust waveguides for light routing. The spatially distinguished layer pseudospin has attracted attention in two‐dimensional electronic materials but it is yet to be discovered in topological photonic structures. Here, all‐dielectric layered photonic topological insulators based on bilayer photonic crystal slabs are reported. The introduction of layer pseudospin offers more dispersion engineering capability, leading to the layer‐polarized and layer‐mixed photonic topological insulators. Their phase transition is demonstrated with a model Hamiltonian by considering the nonzero interlayer coupling. Layer‐direction locking behavior of layer‐polarized photonic topological insulators results in the selective light refraction. High transmission is observed in the bilayer domain wall between two layer‐mixed photonic topological insulators, even when a large defect is introduced. Layered photonic topological insulators not only offer a route toward the observation of richer nontrivial phases, but also open a way for device applications in integrated photonics and information processing by using the additional layer pseudospin. All‐dielectric layered photonic topological insulators are reported based on bilayer photonic crystal slabs. This class of photonic topological insulators is demonstrated in the on‐chip silicon‐on‐insulator platform which is pursued in topological nanophotonics. The introduction of additional layer pseudospin offers more dispersion engineering capability and enriches the nontrivial phases with the finding of layer‐polarized and layer‐mixed photonic topological insulators.